Konsep monoteisme dalam aliran Saivisme : Analisis menurut perspektif Islam / Samsuddin Abd Hamid - Samsuddin , Abd Hamid (2012)
Hinduism worshipping the Lord Brahma, the one seen with three different functions and character through the responsibility of Lord Brahma as the Creator, Lord Vishnu as the Sustainer and Lord Siva as the Destroyer. The Hinduism belief also known as trimurty or thirumoorthi displayed in the form of an aesthetic that is a god illustrated in the beautiful form in accordance with the various attribute of god. The believe of one God or monotheism exists in every stream in Hinduism, for example the Saivism. The Saivism is being emphasized as believe in the only god which is the God Siva. This has been explained and stressed in the Hinduism text as well as in their daily ritual. Based on the concept of monotheism, Hinduism believe that their basic teaching is true like other monotheism religion especially Islam. Some of the methodology used to clarify this research, includes library research and field studies, including an interview with some of Hindus‟ and scholars who are experts on Hinduism. Thus, the concept of monotheism in Hinduism, particularly in the teaching of Saivism is different from the concept of "Tawhid" in Islam. This is because the terminology and epistemological of one and „esa‟ is different and sort of all of this is closely related to the differences of philosophy and teachings in each religion.